Trait association and magnitude of direct and indirect effects on yield in sorghum(Sorghum bicolor L. Moench) genotypes - Gorajana, Nalini Naidu; Gupta, Praveen Kumar; M Elangovan; V, Narsimha Reddy; Gogada, Raghu (Journal of Cereal Research, 2024)
The present investigation was carried out with 65 accessions of sorghum genotypesalong with 3 checks to estimates the association among different traits and magnitude ofdirect and indirect effects on grain yield per plant. Results of correlation analysis pointed outhighly significant and positive association at both phenotypic and genotypic levels by drypanicle weight (rg=0.7, rp=0.698), leaf width (rg=0.657, rp=0.607) followed by moderatelysignificant and positive association by dry matter production (rg=0.54, rp=0.522) and fodderyield (rg=0.535, rp=0.518) with the dependent character grain yield per plant. Themagnitudes of genotypic correlation were found higher than the phenotypic correlation.Partitioning of yield and its component traits at phenotypic levels into direct and indirectcontribution of the traits exhibited highest positive direct effects on grain yield per plantwere dry panicle weight (Ppi=0.697) followed by fodder yield (Ppi =0.053) and 100-seedweight (Ppi =0.028). Hence, these parameters may be considered as selection indices insorghum breeding programmes.